CineAFEP: intervenção educativa no uso de drogas - Matheus, Carolina Bozza [UNESP]; Santana, Flavia Gonçalves [UNESP]; Polli, Larissa Migliatti [UNESP]; Paulino, Gustavo Chagas Lutfala [UNESP]; Martins, Ana Carolina [UNESP]; Silva, Lucas Gonçalves [UNESP]; Pavan, Jacqueline Costa [UNESP]; Cecatti, Clara Pellizzari [UNESP]; Nagai, Ana Carolina Sayuri [UNESP]; Bonifácio, Beatriz Barioni [UNESP]; Chaves, Patricia Cardoso [UNESP]; Aguiar, Bruna Forte [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
Adolescence is a stage surrounded by change, is a confrontational stage of life, the moment that originate curiosity, questions, and new experiences. Even knowing the possible risks young people tend to be exposed to situations that bring a sense of autonomy. It is time that the young looking for their identity, both with familiar examples as the relationships that builds in environments that attends. To try to prevent the young to get involved in situations that may harm you in some way, such as drug use and teenage pregnancy, for example, usually schools and families looking to guide them through educational interventions of various kinds. The CineAFEP is a Faculty of Pharmaceutical Sciences project that seeks to promote awareness actions through films to try to sensitize young people about the thematic.

A adolescência é uma fase cercada por mudanças, é uma fase conflituosa da vida, o momento em que se originam a curiosidade, os questionamentos, e novas experiências. Mesmo sabendo dos possíveis riscos os jovens tendem a se expor a situações que trazem um sentimento de autonomia. É o momento que o jovem procura sua identidade, tanto com exemplos familiares como nas relações que constrói nos ambientes que frequenta. Para tentar evitar que o jovem se envolva em situações que possam o prejudicar de alguma maneira, como o uso de drogas e gravidez na adolescência, por exemplo, normalmente as escolas e familiares procuram orientá-los por meio de intervenções educativas de diversos tipos. O CineAFEP é um projeto da Faculdade de Ciências Farmacêuticas que busca promover ações de conscientização por meio de filmes para tentar sensibilizar os jovens a respeito da temática.
Keywords: Health education; Pharmaceutical care; Illegal drugs; Educação em saúde; Assistência farmacêutica; Drogas ilícitas